2017
DOI: 10.4049/jimmunol.1700904
|View full text |Cite
|
Sign up to set email alerts
|

Rab27-Dependent Exosome Production Inhibits Chronic Inflammation and Enables Acute Responses to Inflammatory Stimuli

Abstract: Extracellular vesicles, including exosomes, have recently been implicated as novel mediators of immune cell communication in mammals. However, roles for endogenously produced exosomes in regulating immune cell functions in vivo are just beginning to be identified. Here, we demonstrate that Rab27a and Rab27b double knockout (Rab27DKO) mice that are deficient in exosome secretion have a chronic, low-grade inflammatory phenotype characterized by elevated inflammatory cytokines and myeloproliferation. Upon further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 47 publications
1
73
0
Order By: Relevance
“…Concretely, tissue specific expression of an exosomal reporter, CD63-pHluorin, revealed that developing zebrafish embryos secrete massive amounts of exosomes in a syntenin-a dependent manner. In this context, the zebrafish model adds to the very few [15,16] in vivo studies of EV biogenesis pathways previously described in vitro [17]. These exosomes (majorly between 80-120nm in size) are secreted from the yolk syncytial layer (YSL) into the blood-stream, a conclusion further supported by in situ electron microscopic analysis of this layer.…”
Section: Biogenesis and Secretionmentioning
confidence: 83%
“…Concretely, tissue specific expression of an exosomal reporter, CD63-pHluorin, revealed that developing zebrafish embryos secrete massive amounts of exosomes in a syntenin-a dependent manner. In this context, the zebrafish model adds to the very few [15,16] in vivo studies of EV biogenesis pathways previously described in vitro [17]. These exosomes (majorly between 80-120nm in size) are secreted from the yolk syncytial layer (YSL) into the blood-stream, a conclusion further supported by in situ electron microscopic analysis of this layer.…”
Section: Biogenesis and Secretionmentioning
confidence: 83%
“…With regard to the intestinal immune balance, the numbers of RAB27A-and RAB27B-positive immune cells increased in the colonic mucosa of patients with active ulcerative colitis (UC) compared to the healthy controls [125,126]. Double knockdown of Rab27A and Rab27B led to interference in protecting mice from T-cell-transfer-induced colitis, which authenticated the crucial role of Rab27mediated EVs in the treatment of IBD [127,128]. All these findings indicate that EV biogenesis acts as a key strategy for the diagnosis and/or therapeutic potential of EVs in IBD.…”
Section: Clinical Potential Of Evs As Biomarkersmentioning
confidence: 90%
“…While Rab27DKO mice showed no response to lipopolysaccharide, response could be restored following exposure to wild-type hematopoietic EVs, but not EVs harvested from miR-155 −/− cells, indicating that vesicle trafficking of miR-155 regulates the innate immune response. 88 …”
Section: Introductionmentioning
confidence: 99%